2016
DOI: 10.1016/j.addbeh.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Comparing adults who use cannabis medically with those who use recreationally: Results from a national sample

Abstract: Objectives Cannabis has been legalized for medical use in almost half of the states in the U.S. Although laws in these states make the distinction between medical and recreational use of cannabis, the prevalence of people using medical cannabis and how distinct this group is from individuals using cannabis recreationally is unknown at a national level. Methods Data came from the 2013 National Survey on Drug Use and Health (NSDUH). All adults endorsing past year cannabis use who reported living in a state tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
123
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(150 citation statements)
references
References 22 publications
21
123
6
Order By: Relevance
“…For example, anecdotal evidence from our study sites suggested that some physicians may be advising patients to adopt vaping as a rout of administration, which might have resulted in higher rates of vaping in this sample. Finally, recent work showed some differences between medical and recreational cannabis users (Lin et al, 2016; Pacula et al, 2016), but we were unable to distinguish between medical and recreational use in the current study.…”
Section: Discussioncontrasting
confidence: 72%
“…For example, anecdotal evidence from our study sites suggested that some physicians may be advising patients to adopt vaping as a rout of administration, which might have resulted in higher rates of vaping in this sample. Finally, recent work showed some differences between medical and recreational cannabis users (Lin et al, 2016; Pacula et al, 2016), but we were unable to distinguish between medical and recreational use in the current study.…”
Section: Discussioncontrasting
confidence: 72%
“…A previous study (Belendiuk et al, 2015) showed that medical cannabis users with insomnia used strains of cannabis with significantly higher concentrations of CBD, which may have affected interpretation of our findings. Finally, recent work showed some differences between medical and recreational cannabis users (Lin et al, 2016; Pacula et al, 2016), but the present study was limited to medical cannabis patients with chronic pain who reported that they were seeking cannabis for medical reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological evidence has indicated that, among past-year cannabis users, about 10% reported using cannabis for medical reasons (Compton et al, 2017); among past-year cannabis users living in states where medical cannabis has been legalized, 17% reported using for medical reasons (Lin et al, 2016). The rapidly changing epidemiology of medical cannabis highlights the importance of research on the potential beneficial and adverse effects of cannabis use (Volkow et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of credible epidemiological estimates, it may be necessary to turn to estimates for the United States, which suggest that as many as one in 7–8 cannabis users in the US might be engaged in medical marijuana use [7]. Whiting and colleagues have prepared a useful systematic review of randomized controlled trials on an array of indications and cannabinoid effects as observed under RCT-controlled conditions [8].…”
Section: The Five Main Rubrics Of Epidemiology As Applied To Cannabismentioning
confidence: 99%